The use of human tissue surrogates in anatomical modeling for gunshot wounds simulations: an overview about “how to do” experimental terminal ballistics - dos Santos, Lucas Meciano Pereira; da Cunha, Marcelo Rodrigues; Reis, Carlos Henrique Bertoni; Buchaim, Daniela Vieira; da Rosa, Ana Paula Bernardes; Tempest, Leandro Moreira; da Cruz, José Augusto Parola; Buchaim, Rogério Leone; Issa, João Paulo Mardegan (Frontiers in Bioengineering and Biotechnology, 2025)
Human tissue simulating materials are currently used in scientific research mainly because they help to avoid possible ethical issues, unlike what happens with studies involving live animals and/or human cadavers. The use of ballistic gelatin as a human soft tissue surrogate stands out, although other types of materials can be used, including polyurethane and polydimethylsiloxane in the simulation of bones and skin respectively, not to mention some computational models that completely replace the physical use of surrogate models for gunshot wound simulation. The use of human tissue surrogates can be useful in reconstructing the dynamics of a crime scene when important forensic traces cannot be found. In the absence of projectiles but in possession of the possible firearm used in the crime, for example, it is possible to verify whether the weapon in question actually fired the fatal gunshot by comparing the injury found on the victim with the injury produced on the simulant material that best represents the anatomical area impacted, as indicated in the literature. Thus, scientific advances in experimental research in terminal ballistics with tissue surrogates can positively impact applied forensic sciences in the search for better technical assistance to the justice system in solving criminal situations.